Analysis of Scalar Doubly Heavy Tetraquark States with QCD Sum Rules - 王志刚 徐艳梅 王慧娟 (Communications in theoretical physics, 2011)
In this article, we perform a detailed study of the mass spectrum of the scalar doubly charmed and doubly bottom tetraquark states using the QCD sum rules.